Sero‐epidemiologic study of influenza A(H7N9) infection among exposed populations, China 2013‐2014. Issue 2 (21st January 2017) - Xiang, Nijuan; Bai, Tian; Kang, Kai; Yuan, Hui; Zhou, Suizan; Ren, Ruiqi; Li, Xiuying; Wu, Jiabing; Deng, Liquan; Zeng, Ge; Wang, Xianjun; Mao, Shenghua; et al.
Abstract : Background: The first human infections of novel avian influenza A(H7N9) virus were identified in China in March 2013. Sentinel surveillance systems and contact tracing may not identify mild and asymptomatic human infections of influenza A(H7N9) virus. Objectives: We assessed the seroprevalence of antibodies to influenza A(H7N9) virus in three populations during the early stages of the epidemic. Patients/Methods: From March 2013 to May 2014, we collected sera from the general population, poultry workers, and contacts of confirmed infections in nine Chinese provinces reporting human A(H7N9) infections and, for contacts, second sera 2‐3 weeks later. We screened for A(H7N9) antibodies by advanced hemagglutination inhibition (HI) assay and tested sera with HI titers ≥20 by modified microneutralization (MN) assay. MN titers ≥20 or fourfold increases in paired sera were considered seropositive. Results: Among general population sera (n=1480), none were seropositive. Among poultry worker sera (n=1866), 28 had HI titers ≥20; two (0.11%, 95% CI: 0.02‐0.44) were positive by MN. Among 61 healthcare and 117 non‐healthcare contacts' sera, five had HI titers ≥20, and all were negative by MN. There was no seroconversion among 131 paired sera. Conclusions: There was no evidence of widespread transmission of influenza A(H7N9) virus during March 2013 to May 2014, although A(H7N9) may have caused rare, previously unrecognized infections among poultry workers. Although the findings suggest that there were few undetected cases of influenza A(H7N9) early in the epidemic, it is important to continue monitoring transmission as virus and epidemic evolve.